3 Archives of Maryland 345 (1885) - (:unkn) unknown (My University, 1658)
Maryland's 1658 militia law required "all persons able to beare Armes within their respective divisions that is of all men between 16 and 60 years of age..." Commanders were directed: "4. That they take an exact view of every man's arms that they well fixed, & that they endeavor to make every householder provide himself speedyly with Arms & Ammunition according to a former Act of Assembly viz 2 pounds of powder and 5 pounds of shot & one good gun well fixed for every man able to bear arms in his house."
Keywords: REQUIRED POSSESSION